If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(x + -8) = -48 Reorder the terms: 8(-8 + x) = -48 (-8 * 8 + x * 8) = -48 (-64 + 8x) = -48 Solving -64 + 8x = -48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '64' to each side of the equation. -64 + 64 + 8x = -48 + 64 Combine like terms: -64 + 64 = 0 0 + 8x = -48 + 64 8x = -48 + 64 Combine like terms: -48 + 64 = 16 8x = 16 Divide each side by '8'. x = 2 Simplifying x = 2
| 4(a+2)=44 | | 5e-2=8 | | 5e-2=18 | | m+n=r | | 11-8x=-109 | | 11x-4=-5 | | y=-1/2x-2 | | 59=7x-11 | | 13+6x=61 | | 3*(4a-3)=-2a-2a+23 | | 8x-7=105 | | 3x(4a-3)=-2a-2a+23 | | x+2/2=7-x+1/3 | | 2x^3/2*-3^-3/2 | | 2(y-3)=20 | | 125*x^5-171*x^4+103*x^3+224*x^2-508*x+240=0 | | x+x+15+4x-22=1139 | | 2(x-7)=6x+10 | | 65-4x=14x+21 | | 10-3=(2x-1) | | 10-3=5(d-4) | | 10x+30=-5x | | 25^(-3/2) | | 4c+8=-88-8x | | Z=ax^2+3by | | 2*x^4-3*x^3+3*x^2-3*x+2=0 | | 2x+12=-13-9x | | 4x-(2x+6)=3x-26 | | x+(15+x)+(-2+4*x)=1139 | | -3(10x-12)+15x=54 | | 4.2x-6.1y+9.7=0 | | (10-x)(6+x)=64 |